In or Out? Exploring the Inconsistency and Permeability of Team Boundaries. (December 2019) - Wimmer, Julia; Backmann, Julia; Hoegl, Martin
Despite the fundamental relevance of team boundaries for team research, scholars have rarely explored their origins and characteristics. Instead, team research commonly assumes the existence of formally defined, stable team boundaries. We challenge this assumption by asserting that beyond formal assignment, team members' individual perceptions of a team's boundaries are driven by individual-level categorization processes and team-level task dynamism. Building on multiple team members' mental representations of team boundaries, we propose that team boundaries are likely mutually inconsistent and vary in their degree of permeability. This permeability and inconsistency serve to clarify how membership change and overlap can induce cognitive and emotional spillovers across teams. The proposed conceptual model links the origins of boundary emergence with their characteristics by explaining how membership structure and dynamics drive the characteristics of team boundaries. This account offers a new perspective on how individual perceptions of work affiliations can shape a team's boundaries.